Comparision of Two Biofilter Media for Developing a Recirculating Aquaculture System - Sarbari Dutta (KUFOS, 2016)
Abstract- Biofilter is the important component of a recirculating aquaculture system. The main role of the biofilter is to remove dissolved waste most importantly ammonia-nitogen (NH3-N) from the culture water. Trickling biofilter is the widely used biofilter type in aquaculture. The efficiency of the trickling biofilter depends on the type of filter media used. The present study aims at comparing the two types of filter media viz.sand and charcoal in designing a simple trickling biofilter used for the farming of Litopenaeus vannamei in a closed recirculatory aquaculture system (RAS). The system water quality was evaluated as a function of filter media to treat waste water produced in a recirculatory aquaculture system. The performance of the recirculatory system was evaluated as a function of the growth and survival of Litopenaeus vannamei stocked in the system. The experiment was conducted using four oval shaped fibre glass tanks of 1000l capacity filled with 500l of water. Two tanks were fitted with charcoal based filter (C1and C2) and two tanks were fitted with sand based filter (S1and S2). 200 numbers of specific pathogen free PL20 of Litopenaeus vannamei was stocked in each tanks. The experiment was carried on for a period of 90 days. The mean pH and nitrite-nitrogen(NH3-N) of both the types of filter tanks were 7.8 and 0.13ppm respectively. There was no significant difference in pH and nitrite-nitrogen (NH3-N) between the charcoal based filter tanks (C1and C2) and sand based filter tanks (S1and S2). The sand based filter tanks (S1and S2) showed significantly lower hardness than charcoal based filter tanks (C1and C2) the average total hardness of sand based filter tanks and charcoal based filter tanks (C1and C2) were 446.11ppm and 504.78ppm respectively. The mean length of the shrimps harvested at the end of 90 days from charcoal based filter tanks and sand based filter tanks (S1and S2) were found to be 8.97cm and 10.03cm respectively. The average weight of the shrimp was 5.70g in charcoal based filter tanks (C1and C2) and 7.27g in sand based filter tanks (S1and S2). Statistical analysis shows that shrimps in sand based filter tanks (S1and S2) shows higher growth rate than shrimps in charcoal based filter tanks (C1and C2). The survival rate in sand based filter tanks (S1and S2) was also higher i.e. 47.5% and charcoal based filter tank (C1and C2) was 39%. However, the best survival of 72% and growth in terms of average length 10.16 cm and average weight of 7.8g was obtained in Litopenaeus vannamei grown in a circular tank fitted with a coral sand based biofilter.